Reconstruction of Natural Smile and Splinting with Natural Tooth Pontic Fiber-Reinforced Composite Bridge - Maryam S. Tavangar; Fatemeh Aghaei; Massoumeh Nowrouzi (Case Reports in Dentistry)
Teeth replacement is challenging in old patients with severe periodontal disease, limiting prosthetics treatment options. Here, we report a fiber-reinforced composite (FRC) resin bridge using natural tooth pontic in a patient with severe periodontitis. A 60-year-old lady complaining of teeth mobility was diagnosed with severe periodontitis, recession, bone loss, and crowding in the anterior maxillary teeth. Due to a hopeless periodontal prognosis, lateral incisors were extracted and sectioned using a cylindrical diamond bur. The pulp chamber was debrided and filled with self-adhesive flowable composite resin. After three weeks, the pontics were fixed in proximal contact areas, and the FRC bridge was fabricated directly using the resin fiber strip followed by occlusion adjustment, finishing, and polishing. Esthetic, occlusion, and periodontal status were re-evaluated after six months. Here, FRC using natural pontic could successfully reconstruct a natural smile, splint the adjacent teeth, eliminate crowding, and provide stable occlusion. Therefore, this method may be considered for similar cases.